Kantor Sewa Di Pekanbaru Dengan Pendekatan Arsitektur Hijau - Epriga, M Arseli; Susilawati, Mira Dharma; Aldy, Pedia (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Pekanbaru is the capital of Riau province which became one of the provinces whose economic growth is very rapid. From a small economic sector even to business and foreigninvestors are in Pekanbaru. Pekanbaru also has become a destination town of investors both from within the country and also abroad have been widely developed in Pekanbaru. However the facilities and space requirements to support the economy so is slightly. Therefore, the rental office is becoming one of the alternatives for developing the economic sector in Pekanbaru. In the design of the rental office, applied design approach emphasizes the principles of green architecture withthe aim of building that is designed into the building to minimize bad influence on the environment, nature, and human and produce a better and more healthy. However, to support this design is also applied in the concept of "integrated green office" which is a concept with a combination of some ofthe supporting elements of green architecture in the form of orientation of the sun, the air, environment, footprint and also the structure will be a unified in whole of the building. Furthermore by applying green architecture design strategies according to Alison G. Kwok form of: (1) Envelope relating to scoper building; (2) Lighting associated with exposure; (3) Cooling associated with refrigerant; (4) Energy production relating to energy production; (5) Water and waste associated with water using. From all that it will make the design of the rental office building is becoming environmentally friendly, save energy, healthy and also good for the environment, the using and also for the building it self. With site area is 3.2 ha and building area 49.383,74 M2.Keywords: Rental office. Green Architecture, Integreted Green Office, Design Strategy Alison G. Kwok